Factors affecting time off work in patients with traumatic hand injuries—A bio-psycho-social perspective. Issue 10 (October 2018) - ,; Best, C.; Dölz, B.; Drummer, N.; Franz, A.; Weißenberg, K.; Müller, W.-L.; Siemers, F.; Betz, C.; Franz, A.; Hanebuth, G.; Sauerbier, M.; et al.
Abstract: Hand injuries are common and can result in a long time off work. To analyse and identify factors affecting time of work, a holistic view on patients is needed. World Health Organization's International Classification of Functioning, Disability and Health (ICF) with its bio-psycho-social perspective provides such a holistic view. The purpose of this study is to analyse time off work in patients with traumatic hand injuries and to identify factors affecting time off work from a bio-psycho-social perspective. We used factors derived from the ICF Core Set for Hand Conditions to predict time off work by applying Cox regression analyses and Kaplan-Meier method using data of a multicentre prospective study in nine German Level 1 hand trauma centres. In total, 231 study participants with a broad range of hand injuries were included. From these, 178 patients (77%) returned to work within 200 days. Impairments in mobility of joint functions and sensory functions related to temperature and other stimuli as well as higher hand strain at work led to extended time off work. Gender, fine hand use and employment status additionally influenced time off work in sub-models. Our results demonstrate that a bio-psycho-social perspective is recommended when investigating time off work.